REBRANDING MENTARI BOOKS MELALUI EVENT 360DEGREE MENTARI - Rana Hana (Jurnal Visi Komunikasi, 2017)
Rapid changes in the business world make brand owners think of strategic steps to continue to exist and develop. A brand that has long been known by the public is not guaranteed to be at the forefront. Therefore, efforts to revitalize the brand are inevitable so that existing brands are able to maintain their business. One effort to revitalize the brand is by doing rebranding. Rebranding is not just a change of logo, but rebranding also includes changes in messages, changes in the approach to consumers, the provision of new services, or even changes in what is promised to consumers. The benefits of brand rebranding are not just the design of a company logo. The purpose of this research is to find out how rebranding is done by companies using Special Event media. As well as ascertaining whether this Special Event is appropriate as a means of Rebranding. The results of this study will explain the company's reasons for choosing Events as a means of rebranding, in addition, researchers will also explain and describe how the series of activities in the event in communicating rebranding. And will explain how the community responded to the event that the company has done in this manner. This study concludes that the event is an appropriate means for rebanding the company because the message delivered in an event will be directly received by the customer so that the company carries out effective communication to the customer.